2012
DOI: 10.1103/physreve.85.066125
|View full text |Cite
|
Sign up to set email alerts
|

Rare-region effects in the contact process on networks

Abstract: Networks and dynamical processes occurring on them have become a paradigmatic representation of complex systems. Studying the role of quenched disorder, both intrinsic to nodes and topological, is a key challenge. With this in mind, here we analyze the contact process (i.e., the simplest model for propagation phenomena) with node-dependent infection rates (i.e., intrinsic quenched disorder) on complex networks. We find Griffiths phases and other rare-region effects, leading rather generically to anomalously sl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 62 publications
(122 reference statements)
6
93
0
Order By: Relevance
“…References [16,18] concluded that finite topological dimension is a necessary condition for observing Griffiths phases and activated scaling in the case of the basic model of nonequilibrium system, the contact process. In the case of CP on certain weighed networks, numerical evidence was shown for generic power laws, but in the thermodynamic limit this phase seems to disappear and a smeared phase transition exists, due to the infinite-dimensional correlated rare regions [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…References [16,18] concluded that finite topological dimension is a necessary condition for observing Griffiths phases and activated scaling in the case of the basic model of nonequilibrium system, the contact process. In the case of CP on certain weighed networks, numerical evidence was shown for generic power laws, but in the thermodynamic limit this phase seems to disappear and a smeared phase transition exists, due to the infinite-dimensional correlated rare regions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the CP, as well as other processes [8,9], have shown that quenched disorder in networks is relevant in the dynamical systems defined on top of them. Very recently it has been shown [16][17][18] that generic slow (power-law or logarithmic) dynamics is observable by simulating CP on networks with finite d. This observation is relevant for recent developments in dynamical processes on complex networks such as the simple model of "working memory" [19], brain dynamics [20], social networks with heterogeneous communities [21], or slow relaxation in glassy systems [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the CP on complex networks, it has recently been shown that an intrinsic quenched disorder 3 defined by a varying control parameter λ i , can induce GPs and other RR effects on random Erdős-Rényi networks [30] below (and at) the percolation threshold [17][18][19]. The authors in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of network disorder have recently been extended one step further, in a series of papers [17][18][19] dealing with the possibility of observing Griffiths phase (GP) and rare-region (RR) phenomena [20,21] at the phase transition of the CP on complex networks. 1 In case of regular lattices it is well known that quenched disorder 2 can strongly alter the behavior of a phase transition, imposing an anomalously slow relaxation [23].…”
Section: Introductionmentioning
confidence: 99%